Source Apportionment of Aerosol Ammonium in an Ammonia‐Rich Atmosphere: An Isotopic Study of Summer Clean and Hazy Days in Urban Beijing. Issue 10 (28th May 2018) - Pan, Yuepeng; Tian, Shili; Liu, Dongwei; Fang, Yunting; Zhu, Xiaying; Gao, Meng; Wentworth, Gregory R.; Michalski, Greg; Huang, Xiaojuan; Wang, Yuesi
Abstract: Aerosol ammonium (NH4 + ) can be a major component of fine particles, especially during severe haze episodes. The abatement of ammonia (NH3 ) emissions is important for reducing fine particles, but NH3 sources remain poorly constrained and are largely unregulated in China and most other regions. This study uses stable isotopes to interpret the role NH3 sources play in generating different sized NH4 + aerosols in Beijing between 21 June and 4 July 2013 with fine particle concentrations of 20–242 μg/m 3 . The concentrations and nitrogen stable isotope composition of aerosol NH4 + (δ 15 N‐NH4 + ) were both elevated during the five haze episodes that were sampled. These increases were driven by enhancements in the fine mode as opposed to substantial increases in the coarse mode aerosol. After accounting for the isotope fractionation that occurs during gas‐to‐particle partitioning (17.7‰ to 28.2‰), the "initial" (prepartitioning) δ 15 N‐NH3 values were estimated to be −35‰ for a clean period (i.e., a nonhazy day) and ranged from −14.3‰ to −22.8‰ for hazy days. Source apportionment using the "IsoSources" isotopic mixing model indicated that the dominant contribution to NH3 shifted from agricultural sources during the clean period (86%) to fossil fuel emissions (54%–81%) during hazy days and when back trajectories rotate from the northwest to the west and/or south. These results together suggest that even in summer, fossil fuel‐related sources from Beijing and the surrounding areas are the major source of NH3 during haze events and that controlling these sources may be important for alleviating particulate matter pollution. Key Points: Nitrogen stable isotope composition of ammonium in fine particles was higher on polluted days than during a clean period Substantial isotopic exchange occurred during haze episodes with excess ammonia Agriculture and fossil fuel combustion dominate urban ammonia sources during clean and hazy days, respectively